2022
DOI: 10.1038/s41420-022-01290-0
|View full text |Cite
|
Sign up to set email alerts
|

DYRK3 phosphorylates SNAPIN to regulate axonal retrograde transport and neurotransmitter release

Abstract: Among the five members of the dual-specificity tyrosine-phosphorylation-regulated kinase (DYRK) family, the cellular functions of DYRK3 have not been fully elucidated. Some studies have indicated limited physiological roles and substrates of DYRK3, including promotion of glioblastoma, requirement in influenza virus replication, and coupling of stress granule condensation with mammalian target of rapamycin complex 1 signaling. Here, we demonstrate that serum deprivation causes a decrease in intracellular DYRK3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The retrospective analysis of a sizable SOC cohort revealed that elevated DYRK3 expression is independently associated with adverse overall survival outcomes. Our findings align with emerging research suggesting DYRK3 as a crucial player in cancer biology [ 9 ]. While DYRK3 has been implicated in various malignancies, its specific role in ovarian cancer remained largely unexplored.…”
Section: Discussionsupporting
confidence: 91%
“…The retrospective analysis of a sizable SOC cohort revealed that elevated DYRK3 expression is independently associated with adverse overall survival outcomes. Our findings align with emerging research suggesting DYRK3 as a crucial player in cancer biology [ 9 ]. While DYRK3 has been implicated in various malignancies, its specific role in ovarian cancer remained largely unexplored.…”
Section: Discussionsupporting
confidence: 91%
“…Links between impaired autophagy and disease are evident in neurodegenerative diseases. RT is essential for the trafficking of autophagic vacuoles from distal locations in neurons to the soma, where most lysosomes reside for autophagic clearance [124,132]. Disrupted RT was shown by Tammineni et al to promote autophagic stress in the context of AD [124].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%